Increased On-Time In-Full orders rate in a mass-consumption warehouse by applying Lean Warehouse tools: A case Study (LACCEI, 2024)
The FMCG sector is developing globally and has maintained exponential growth in recent years. However, this growth is hampered by various challenges and issues affecting customer satisfaction, leading to a significant revenue loss for companies. In this area, companies in the sector aim to reduce the rate of orders not delivered on time and complete to increase customer satisfaction and minimize lost sales. In this context, the problem that causes the most significant economic impact on the company under study is the low rate of the OTIF indicator. Implementing a model based on the Lean Warehouse methodology is proposed to face this challenge by applying Slotting, Standardized Work, and Slotting. The study focused on the standard products (Packaged Jelly), analyzed, and diagnosed the delivery process, identified and quantified the root cause of the problem, and subsequently provided tools to attack them. Ultimately, the proposed model successfully increased the OTIF indicator by 28.94%. Key results include a 20.22% increase in the inventory accuracy indicator, a 41.53% decrease in the time to reach the product location, and a 12.02% increase in operator efficiency in the picking process. In this context, a precedent is set to contribute to optimizing the processes of the company's division and maximizing customer satisfaction.